Role and place of postgraduate education in the national doctors' training system - Lysenko Oleksandra (Borys Grinchenko Kyiv Metropolitan University, 2015)
This article highlights the presented stages of medical education in Ukraine (6 years of university training to obtain qualification of Medical Doctor, 1-3 years of internship to obtain qualification of Doctor-Specialist and the additional training opportunity to improve the professional skills in clinical residency for about two years); the features of their post-graduate education at the present stage; characterized compulsory stage of primary specialization in one of the 30 specialtiesin a period of internship whichlasts from 1 to 3 years; presented peculiarities of the internship training process, especially given explanations about theoretical and practical parts of interns' activity; the features of interns' intermediate and final certification characterized; marked practical orientation of primary specialization and a mandatory list of practical skills needed to master; explained the possibilities of acquiring further qualifications in a particular specialty in clinical ordinary; noted the possibility of narrow specialty obtaining by specialization passing and the opportunity of some thematic improvement highlights;submitted a reform plan on postgraduate training, including decreasing internshipspecialties and medical residency introduction as a step acquisition specialization after the internship; characterized obligatory training for pre-certification and certification of passage to assign or confirm the medical qualification category at least once in five years.